Conducting Qualitative Research on Race - Lorenzo Bowman (Adult Education Research Conference, 2007)
The “race-of-interviewer” effect is well documented in the research literature. Research designs that seek to control for these effects do not eliminate other methodological issues such as the impact of social desirability on the responses of White participants, and interviewer-respondent rapport among Black participants.